Re-envisioning a “skills framework” to meet 21st century demands: What do young people need? - Buasuwan, Prompilai; Suebnusorn, Wanwisa; Butkatunyoo, Oraphan; Manowaluilou, Nongluck; Kaewchinda, Marid; Lalitpasan, Usanee; Srilapo, Nart; Sarnswang, Sudarat; Suksiri, Weeraphat; Wiboonuppatham, Rangsun; Sripongpankul, Saipan (Frontiers in Education, 2022)
Today's children and youth face rapidly changing landscapes in all aspects of life, posing more challenges to the well-being of future generations and the success of the global commitment to SDGs. The skills framework project was introduced to reexamine the 'Life skills'/ Skills Education Framework to guide the direction of 21st Century Skills in Thai Education. There is a long tradition of skills frameworks developed and proposed by various organizations. However, in re-envisioning one for Thailand's young people, it was crucial to involve them in the process. This paper describes a design-thinking approach to developing a skills framework involving stakeholders' voices and, crucially, Thai children and youth. The paper argues that any skills framework for the 21st Century must include young people's values and aspirations. This study shows that while Thai children and adolescents share common interests, differ in their focus on required skills, and have the vision to make Thailand a prosperous nation, they are also challenging some core values. The proposed basic education 'skills framework' is designed to be comprehensive and flexible, encompassing a global skills framework to meet 21st century needs and support global commitments to the SDGs, while also reflecting Thailand’s and the diverse needs of stakeholders, especially young people. It also emphasizes the principles of applicability, adaptability, and relevance that apply to each child and reflects the aspirations and dreams of its young people in the context of a changing environment and future demands.